Multi detector computerized tomography scans aid in the staging of Head and Neck cancers - Bamidele Kolude; Sigbeku Opeyemi; Adeniji-Sofoluwe Bamidele; Adeosun Aderemi (Universidade Estadual de Campinas, 2017)
Introduction/Objectives: To assess the efficacy and correlation of MDCT scans in the clinical staging of patients with HNCs prior to therapeutic intervention. Methodology: Thirty-four HNCs were studied according to the 2005 WHO. Clinical AJCC 6th edition & radiological staging. Results: 14 Squamous Cell Carcinoma (SCC 41.2%) mean age 49.4 + 14.7 years, 13 Nasopharyngeal Carcinoma (NPC 38.2%) mean age 37.1 + 20.5 years, 3 Odontogenic Carcinoma (ODC 8.8% made up of 2 cases ameloblastic carcinoma 5.9% and 1 case of ameloblastic carcinosarcoma 2.9%). Others cases were 3 Adenocarcinoma (8.8%) and 1 Sinonasal Carcinoma NC (2.9%). Mean age insignificant according to gender (p = 0.342). Sensitivity, specificity, positive & negative predictive values and accuracy of clinical and radiological nodal involvements were: (47.4%; 80%; 61.8%; 75%; 54.5%) & (78.9%; 93.3%; 85.3%; 93.8%; 77.8%) respectively. Difference between clinical and radiological stages was statistically significant (X2= 260.8; p=0.01). There was a low but positive correlation between the clinical and radiologic stages (Pearson's correlation r = 0.6). Conclusion: MDCT was significantly more accurate than clinical examination in the TNM of HNCs using AJCC/UICC TNM guidelines. Authors recommend MDCT as first line imaging technique in resource limited settings.